Experimental study of strong field ionization and high harmonic generation in molecules - Vajdi, Aram (Kansas State University, 2015)
This report includes the experimental details and results of two experiments. The first experiment addresses carrier envelope phase (CEP) effects in higher order harmonic generation (HHG), and the second experiment is a pump-probe experiment on CO₂ molecules using ultrashort laser pulses. Ultrashort laser pulses that are only a few optical cycles long are of interest for studying different atomic and molecular processes. The CEP of such a pulse is an important parameter that can affect the experimental results. Because the laser pulses we used in the HHG experiment have random CEP, we tagged a given harmonic spectrum with the CEP of the fundamental laser pulse that generated it by measuring both shot-by-shot. The first chapter of this report is about the experimental details and the results we got from our CEP-tagged HHG experiment that enabled us to observe the interference of different quantum pathways. In the second experiment, discussed in the second chapter of this report, we tried to study the structure of the CO₂⁺ ion created by strong field ionization in a pump-probe experiment. For this experiment, we used an ultrashort laser pulse to ionize CO₂ molecules, and after various time delays we probed the ionic wave packet by ionizing CO₂⁺ with another ultrashort laser pulse. By performing Fourier analysis on the delay-dependent CO₂⁺⁺ yield, we were able to identify the populated states of CO₂⁺.
Keywords: High harmonic generation; Strong field ionization; Atomic Physics (0748); Molecular Physics (0609); Optics (0752)